Coherent spectroscopies on ultrashort time and length scales - Schneider C.; Rewitz C.; Razinskas G.; Pfeiffer W.; Melchior P.; Kramer C.; Huang J.-S.; Keitzl T.; Hecht B.; Goetz S.; Geisler P.; Fischer A.; et al. (EPJ Web of Conferences, 2013)
Three spectroscopic techniques are presented that provide simultaneous spatial and temporal resolution: modified confocal microscopy with heterodyne detection, space-time-resolved spectroscopy using coherent control concepts, and coherent two-dimensional nano-spectroscopy. Latest experimental results are discussed.